Pelatihan Pemanfaatan Kecerdasan Buatan untuk Proses Pembelajaran di SMK Telkom Sidoarjo - Muhsin, Muhammad; Rachmaningrum, Nilla; Kuntjoro, Tri Agus Djoko; Ramya, Vidira Anindita; Nugraha, Nicholas Ardi; Jadmiko, Puguh Chondro; Cahyo, Muhammad Dwi; Putri, Wafiqoh Dwi Oktaviana (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The use of artificial intelligence has become common, including in the learning process. In the digital era, the use of artificial intelligence for education has both potential and risks. Therefore, an appropriate understanding is needed for the use of artificial intelligence in education. This is to ensure that artificial intelligence is used effectively, efficiently, and appropriately. In this article, the community service team organized artificial intelligence training for the learning process at SMK Telkom Sidoarjo. Before the training, an observation was conducted on the general and specific conditions. Then the team compiles the module according to the results of the observation. The training includes various appropriate artificial intelligence tools and ethics in their use. The training was evaluated using a questionnaire and showed high satisfaction with an average score of 92.96%.